Pediatric and Adolescent Plastic Surgery for the Clinician - Vlahovic, Aleksandar M.; Haxhija, Emir Q. (Springer International Publishing : Imprint: Springer, 2017)
This book describes plastic surgery treatments in children for e.g. cleft lip and palate, polydactyly and syndactyly, pigment lesions, benign and malign skin and soft tissue tumors, and vascular anomalies. Every chapter starts with a short introduction, followed by sections on patient evaluation, treatment options and postoperative care. Supporting images and pitfalls are also included. Based on the authors experience, the book offers pediatric plastic surgeons a valuable guide in their everyday work, while also introducing interested practitioners to the field. Pediatric plastic surgery is a specific field of surgery which includes reconstructive and aesthetic-cosmetic procedures in children. The majority of procedures are reconstructive in nature, making aesthetic considerations especially important. As aesthetic procedures in children are not so frequent, only a small group of clinicians are familiar with this part of surgery.
Keywords: Medicine.; Pediatric surgery.; Plastic surgery.; elektronické knihy; electronic books